1988
DOI: 10.2307/1143473
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Differences in Attitudes toward Policing: Evidence for a Mixed-Strategy Model of Policing in a Multi-Ethnic Setting

Abstract: There are prevalent in society two general conceptions of the duties of the police officer. Middle class people feel that he should enforce the law without fear or favor. Cornerville people and many of the officers themselves believe that the policeman should have the confidence of the people in his area so that he can settle many difficulties in a personal manner without making arrests. These two conceptions are in a large measure contradictory.' William Foote Whyte made these general observations more than f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
85
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(95 citation statements)
references
References 0 publications
8
85
2
Order By: Relevance
“…However, the impact of individual class does not persist when neighborhood class level is included in the analysis, suggesting that it is neighborhood class status, rather than individual class status, that matters more in measuring satisfaction with police. This finding echoes the results from a handful of previous studies (i.e., Dunham & Alpert, 1988;Weitzer, 1999Weitzer, , 2000. Moreover, neighborhood class level is also pivotal in conditioning the effect of individual racial background on satisfaction with police.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…However, the impact of individual class does not persist when neighborhood class level is included in the analysis, suggesting that it is neighborhood class status, rather than individual class status, that matters more in measuring satisfaction with police. This finding echoes the results from a handful of previous studies (i.e., Dunham & Alpert, 1988;Weitzer, 1999Weitzer, , 2000. Moreover, neighborhood class level is also pivotal in conditioning the effect of individual racial background on satisfaction with police.…”
Section: Discussionsupporting
confidence: 87%
“…For instance, Dunham and Alpert (1988) found that residents of one middle-class and one lower-class predominantly Black neighborhood generally held more negative attitudes toward police than those who lived in the White neighborhood, but there were attitudinal variations between Blacks in the two Black neighborhoods. They thus concluded that neighborhood differences in attitudes toward police went beyond traditional racial distinctions and that the main factors defining neighborhoods included both racial make-up and socioeconomic status.…”
Section: Racial Composition and Classmentioning
confidence: 99%
See 2 more Smart Citations
“…Dunham and Alpert (1988), studying five ethnic and racially distinct neighborhoods in Miami, found a high degree of consensus within each neighborhood about the police and police practices. Residents of two distinctly different black neighborhoods (lower income versus middle income) held less favorable views on the issues of police use of discretion (whom the police would stop or arrest) and the police department's overall demeanor (respectful versus disrespectful) than did residents of white and Cuban neighborhoods.…”
Section: Introductionmentioning
confidence: 99%